فعالية التحصيل الأكاديمي مقارنة بالخبرة الميدانية في تحسين كفاءة مدربي كرة القدم - قادم, العيد (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
هدفت هذه الدراسة إلى الكشف عن العلاقة بين التحصيل الأكاديمي والخبرة الميدانية في تحسين كفاءة المدرب الرياضي، من خلال دراسة ميدانية لعينة من مدربي كرة القدم متكونة من 40 مدرب. وقد انطلقت الإشكالية من ملاحظة وجود تباين في الكفاءة بين المدربين ذوي التكوين الأكاديمي، والمدربين الذين يعتمدون على الخبرة فقط، مما طرح تساؤلات حول مدى فعالية كل من الجانبين، أو ما إذا كان الجمع بينهما يمثل الخيار الأمثل. اعتماد الباحث المنهج الوصفي التحليلي، وتوظيف الاستبيان كأداة رئيسية لجمع البيانات من عينة قصدية من المدربين. وقد شملت محاور الاستبيان أربعة أبعاد رئيسية: التخطيط، التنفيذ، التعامل مع اللاعبين، وتقدير الفعالية العامة للمدرب، وبعد جمع الاستبيان وتفريغه حصلنا على مجموعة من النتائج حيث تمت معالجتها إحصائيا باستخدام برنامج SPSS 27لاستخراج النسب المئوية وتطبيق اختبار كاي مربع (χ²) ولضمان صدق وثبات أداة البحث، قام الباحث بحساب معامل الثبات (ألفا كرونباخ) لكل محور باستخدام برناجم Excel، من بين أهم النتائج التي توصلة إليها بعد التحليل أنه هناك وجود علاقة دالة إحصائيا بين نوع التأهيل (أكاديمي أو ميداني) وبين كفاءة المدرب، حيث خلصت هذه الدراسة إلى أن فعالية المدرب لا تتأتى من أحد الجانبين بمفرده، بل من تكاملهما، وأوصت بضرورة إعداد برامج تكوين شاملة تجمع بين الجانب الأكاديمي والممارسة التطبيقية، لضمان تطوير كفاءات مهنية متعددة لدى المدربين. انطلاقا من هذه المعطيات قسمة هذا البحث إلى قسمين: جانب نظري يحتوي على الباب الأول المتكون من أربعة فصول وهي: - الفصل الأول التحصيل الأكاديمي. - الفصل الثاني:الخبرة الميدانية. - الفصل الثالث: التكامل بين التحصيل الأكاديمي والخبرة الميدانية - الفصل الرابع: كفاءة المدرب في تطوير اللاعبين. بينما الباب الثاني المتكون من الجانب التطبيقي الذي يحتوي على فصلين هما: - الفصل الأول : منهجية البحث وإجراءاته الميدانية: وتتضمن منهج البحث و الأداة المستخدمة في البحث ومجتمع الدراسة وخصائص العينة. // // // // Abstract: This study aimed to explore the relationship between academic achievement and field experience in enhancing the competence of sports coaches, through a field study conducted on a sample of 40 football coaches. The research problem stemmed from the observation of a noticeable discrepancy in coaching competence between academically trained coaches and those who rely solely on practical experience, raising questions about the effectiveness of each side or whether a combination of both represents the optimal approach. The descriptive-analytical method was adopted, and a questionnaire was used as the primary tool for data collection from a purposive sample of coaches. The questionnaire addressed four key dimensions: planning, execution, interaction with players, and the general assessment of coaching effectiveness. After collecting and organizing the responses, the data were statistically processed using SPSS 27 software to extract percentages and apply the Chi-square test (χ²). To ensure the validity and reliability of the research tool, Cronbach’s Alpha coefficient was calculated for each dimension using Excel software. Among the key findings revealed by the analysis was the presence of a statistically significant relationship between the type of qualification (academic or field-based) and the coach's competence. The study concluded that coaching effectiveness does not result from either dimension alone but rather from their integration. It recommended the design of comprehensive training programs that combine academic education with practical field experience to ensure the development of well-rounded professional coaching competencies. Based on these findings, the research was divided into two main sections: - Theoretical section, which includes the first part composed of four chapters: • Chapter One: AcademicAchievement • ChapterTwo: Field Experience • Chapter Three: The Integration between Academic Achievement and Field Experience • Chapter Four: Coach Competence in Developing Players - Applied section, which includes the second part composed of two chapters: • Chapter One: Research Methodology and Field Procedures, covering the research method, tools, population, and sample characteristics. • Chapter Two: Analysis and Interpretation of the Results Obtained from the Study
MES-2025-7
Keywords: التحصيل الأكاديمي- الخبرة الميدانية - الكفاءة المهنية للمدرب الرياضي // // Academic Achievement – Field Experience – Professional Competence of the Sports Coach